Application of the lipofection method to transform gene into the cells of the cyanobacterium - species Spirulina platensis - Hoai Thu, Ngo Thi; Hong, Dang Diem; Aiba, Sei-ichi; Kawata, Yoshikazu (Academia Journal of Biology, 2014)
Spirulina platensis was a commercially cultured cyanobacterium spcies, having biomass up to 3.000 tons in a year and used as health food and animal feed. If we could draw its potential, we could apply S. platensis to solve environment problems. S. platensis produced valuable materials such as g-linolenic acid, bioplastic etc. To increase the content of these materials, the recombinant DNA technique was most important, but its application has just been started. At present, to transform gene into Spirulina cells, only the electroporation method was applied for this purpose. The lipofection method was used widely for transfection. It had advantages for its convenience, efficiency and safety but its application was limited to culture mammalian cells. Recently, we found E. coli and S. platensis could be transformed by lipofection method. We investigated conditions to transform S. platensis with DOTAP liposomal transfection reagents. We used the pHSG397 vector with cat to transform S. platensis. The transformed Spirulina cells could survive in the condition of chloramphenicol concentration more than 0.5 mg/ml for 4 weeks. The transformation efficiency of the lipofection method was 4 - 15 times better in comparison with the electroporation method, dependently on applied vetors (such as close or open vector cutted used by the enzyme EcoRI).